Desapego emocional y su repercusión en la salud mental de una adolescente de 12 años de edad del cantón Urdaneta - Apraez Zambrano, Nayelli Stefani (2023)
The present document tries to determine the influence of emotional detachment in the mental health of a 12 year old girl from Urdaneta County, therefore, reliable instruments and resources have been used to obtain a presumptive diagnosis, based on the symptomatologies that were present in the patient since the first therapeutic encounter with her, therefore, it was established to work with her during six sessions, where an initial interview was used to collect the patient's data, In the same way, direct observation was used, thus facilitating the collection of essential data such as body information, body tonality, movement and mobility, also information was collected on the adolescent from her childhood to her present age, to finalize this process, psychometric reagents were applied, which helped to corroborate the hypotheses, thus reflecting the following coding: CIE 10 F93. 0 and in its equivalent DSM 5 code 309.21; corresponding to a separation disorder, which causes dysfunctions in the cognitive, affective, behavioral-social and somatic areas. Finally, a treatment scheme based on Cognitive Behavioral Therapy was applied, through which it was possible to work on the emotions and the eradication of the automatic thoughts presented by the patient.